ANALISIS HUKUM TERHADAP PERKAWINAN PAKSA YANG DILAKUKAN ORANG TUA TERHADAP ANAK (STUDI KOMPILASI HUKUM ISLAM) - imam, fauzi; Ilyas, Sitti Kumala; Lasori, Sitti Alfisyahrin; Andini, Nur Qalbi (Fakultas Hukum Universitas Ichsan Gorontalo, 2025)
Abtract: The purposes of this study are objective purpose and subjective purpose. 1) The objective purposes are (a) to analyze the act of forced marriage committed by parents against children and (b) to analyze the acts of violence committed by parents against children. 2) The subjective purposes are (a) to increase the knowledge and insight of the author in handling forced marriage committed by parents against children, (b) to obtain complete data on forced marriage committed by parents against children, and (c) to be able to apply all the knowledge and theories that obtained by the author. The method used in this study is an empirical juridical method that requires going directly to the field and using primary data sources. The approach taken uses juridical methods and sociological approaches, namely the juridical approach method in which the study approach carried out is to examine a problem in terms of law and its systematic and as a guide to the rules used as analysis basis of legal symptoms that arise. The results of this study indicate that: (1) The practice of forced marriage of children that occurs in Kolami Village is not in line with the Compilation of Islamic Law (KHI) in Article 15 that explains: (1) For the benefit of families and households, marriage may only be carried out by prospective brides who have reached the age stipulated in Article 7 of Law No. 1 of 1974. (2) Forced marriage that occurs in Kolami Village has several negative impacts, namely physical & psychological illness. It is because the woman forced to marry has a deep trauma.